A new subspecies of Xixuthrus from Papua New Guinea (Coleoptera: Cerambycidae, Prioninae) - Missori, Paolo; Ercoli, Lucia (Zootaxa, 2018)
The prionine genus Xixuthrus consists of species among the largest cerambycids in the world, attaining sizes more than 150 mm. The genus occurs in the Australo–Indo–Pacific regions with 18 species, six of which are found in New Guinea (Xixuthrus arfakianus, granulipennis, helleri, lameerei, microcerus axis, thomsoni). Their habitat is limited to primeval rainforests, and in many areas, it is under threat because of logging and human deforestation. The life cycle of these beetles is unknown, and they remain elusive and mysterious because of the limited accessibility to specimens living in dense rainforest of middle–high volcanic regions with inaccessible steep slopes affected by high humidity, fog, and heavy rainfall. The new subspecies described here was collected in the centre of Papua New Guinea, where many beetles are to date undescribed.